Solubility and crystallisability of the ternary system: Hexadecane and octadecane representative in fuel solvents. (15th August 2018) - Tang, Xue; Kaskiewicz, Peter L.; Camacho Corzo, Diana M.; Lai, Xiaojun; Roberts, Kevin J.; Dowding, Peter; More, Iain
Abstract: The solubility and crystallisability of a range of binary mixtures of n-hexadecane (C16 H34 ) and n-octadecane (C18 H38 ), as the predominant alkanes present in hydrotreated vegetable oil (HVO), from three representative fuel solutions (dodecane, toluene and kerosene) is presented. The dissolution (saturation) and crystallisation (supersaturation) points of the solutions are measured using poly-thermal methods utilising turbidometric detection over four concentrations from (192 g/l to 400 g/l). The data reveals the existence of more soluble, less stable crystal structures that form from the alkane mixtures, when compared to the stable triclinic crystal structures formed from the single solute component solutions. An increased carbon chain length results in lower solubility for all three solvents and the solvent type is not found to have any significant effect on the solid forms produced from the mixtures. van't Hoff analysis reveals the solvent type to influence the solute solubility with the closest to ideal behaviour being dodecane followed by kerosene and toluene, respectively. This finding is further supported by the calculated dissolution enthalpies and activity coefficients, which are the lowest in dodecane followed by kerosene and toluene. Larger values of activity coefficients are observed for compositions with molar fraction ( y ) = 0.1, 0.5–0.7 C18 H38 which reflect the complex multi-phase formation in the solutions when compared with the more simple binary melt crystallisation system.